Chemoenzymatic synthesis of hygromycin aminocyclitol moiety and its C2 epimer - Carrau, Gonzalo (2018)
This manuscript describes the enantioselective synthesis of the aminocyclitol moiety of the antibiotic hygromycin A in eight steps and 39 % overall yield from a non-chiral starting material. The sequence made use of an initial enzymatic step to transfer chirality to an aromatic ring and was followed by selective organic chemistry transformations (oxidation, pro-tection, azidation, hydrolysis) of the six-membered ring in order to achieve the target. The approach is also amenable to the synthesis of other related unnatural analogues as exemplified by the synthesis of the C2 epimer of the natural aminocyclitol. All the intermediates were fully characterized, and the absolute stereochemistry assigned by spectrometric methods.